Unequal Exceptions: Zoning Relief in New York City, 1998–2017. (June 2022) - Fischer, Lauren Ames; Stahl, Valerie E.; Baird-Zars, Bernadette
Zoning relief, the process of exempting individual properties from land-use regulations, is a widespread yet underexplored planning practice. A mixed-methods analysis of applications to the Board of Standards and Appeals in New York City between 1998 and 2017 examines three clusters of zoning relief. The results suggest a strong relationship between relief and neighborhood socio-political capital and underscore relief as a powerful form of ad hoc planning. Zoning relief practices in New York City deepen inequalities but also facilitate planning goals such as disaster recovery and allowing families to grow in place. Zoning relief has long-lasting consequences on urban development and deserves increased attention from planning scholars.